Penetration of Vegetable Oils into Textured Hair Fibers: Integrating Molecular Matrix Assisted Laser Desorption Ioni-Zation Time-of-Flight Mass Spectroscopy (MALDI TOF/TOF MS) Analysis with Mechanical Measurements - Carolina Botelho Lourenço; Rebeca Mantuan Gasparin; Fernanda Malanconi Thomaz; Renato Grimaldi; Ana Cláudia Paiva-Santos; Priscila Gava Mazzola (Cosmetics, 2024)
The promotion of natural beauty has empowered women with textured hair to embrace their natural hair texture and opt for bleaching as a means of style variation. However, bleaching exacerbates the inherent fragility of this hair type, necessitating treatments to partially restore its mechanical properties. Vegetable oils, renowned for their strengthening properties, were evaluated regarding (I) their ability to penetrate both virgin and bleached textured hair using Matrix-Assisted Laser Desorption Ionization (MALDI) time-of-flight (TOF) analysis, and (II) their effects by way of tensile and fatigue tests. The MALDI–TOF results revealed groups of oil molecules in the cortical region of the bleached textured hair. The tensile test results, in turn, showed that the oil treatments were unable to alter the mechanical properties of the hair. Conversely, the fatigue test showed an increase in resistance in the virgin hair, most likely attributed to a lubrication effect in the outermost portions of the cortex and cuticles. In the bleached hair, a reduction in resistance was noted following the treatment with the oils. Comparative analysis with a previous study on straight hair by our group suggests that external molecules diffuse more homogeneously in straight hair than in textured hair. The unique cortical structure of textured hair creates two areas with distinct diffusion zones, resulting in the irregular distribution of external materials and different effects compared to straight hair.